Adherence to Recommended Preventive Behaviors During the COVID-19 Pandemic: The Role of Empathy and Perceived Health Threat. Issue 4 (29th December 2021) - Morstead, Talia; Zheng, Jason; Sin, Nancy L; King, David B; DeLongis, Anita
Abstract: Background: Coping via empathic responding may play a role in preventive behavior engagement during the COVID-19 pandemic, and unlike trait empathy, is a potentially alterable target for changing health behavior. Purpose: Our goal was to examine the role of empathic responding in preventive behavior engagement during the COVID-19 pandemic, independent of trait empathy and perceived threat of COVID-19. Methods: Participants ( N = 2, 841) completed a baseline survey early in the pandemic, and a follow-up survey approximately 2 weeks later ( M = 13.50 days, SD = 5.61). Preventive health behaviors, including physical distancing and hygiene practices, were assessed at both timepoints. Hierarchical linear regression examined the contributions of trait empathy, perceived threat of COVID-19, and empathic responding at baseline to preventive behaviors at follow-up. Results: Controlling for baseline levels of preventive behaviors and demographic covariates, trait empathy and threat of COVID-19 at baseline were each independently associated with preventive behaviors at follow-up. An interaction between perceived threat and empathic responding indicated that those perceiving high threat of COVID-19 at baseline tended to report engaging in preventive behaviors at follow-up regardless of their levels of empathic responding, whereas for those reporting low levels of perceived threat, higher levels of empathic responding were associated with higher engagement in preventive behavior. Conclusions: When perceived threat of COVID-19 was low, higher empathic responding was associated with increased engagement in preventive behaviors regardless of trait empathy, suggesting that empathic responding can serve as an actionable target for intervention to promote preventive behavior during the pandemic. Abstract : Among those who felt less personally threatened by COVID-19, empathic responding early in the pandemic was associated with increased engagement in WHO-recommended health behaviors.